The Future of Radio Revisited: Expert Perspectives and Future Scenarios for Radio Media in 2025. Issue 1 (2nd January 2017) - Jauert, Per; Ala-Fossi, Marko; Föllmer, Golo; Lax, Stephen; Murphy, Kenneth
Abstract : In 2005–2006 the research group DRACE (Digital Radio Cultures in Europe) performed a study on how 43 people in key positions related to the radio industry in 4 European countries and Canada viewed the future of radio and which delivery technologies they considered would be most successful. In addition, it analyzed the motives and reasons certain technologies were seen as more promising than others. Finally, it presented 4 different future scenarios for radio media. The study was published in the Journal of Radio and Audio Media, May 2008. In 2005 the future of radio was considered much less obvious and clear than it appeared 10 years previously. Instead of a transition from analog to digital audio broad- casting (DAB), there was a selection of alternative technological options for digital audio delivery. When looking back from 2015 and considering the results of expert interviews, the project group about Public Service Media in the HERA project: Transnational Radio Encounters found interesting perspectives in replicating this study—now looking forward to 2025. By using the same questionnaire and interviewing the same experts (or new persons in the same positions) they could compare the predictions with the present situation, looking for technological, regulatory, policy based, and user-oriented contexts. Furthermore, they could ask the experts to look 10 years forward to 2025. Besides from the interviews, desk studies were performed in order to explore the national similarities and differences as background for the analysis of the scenarios for the 2015 and 2025 studies. This comparative study involves Denmark, Finland, Germany, Ireland, and the UK.